Modeling and control design of a bronchoscope robotics system - Yuhua Song; Lifeng Zhu; Jinfeng Li; Cheng Wang; Aiguo Song (EngMedicine)
For the pulmonary nodule biopsy problem, this paper investigates an intervention robotics system based on the bronchoscope. To achieve precise control of the system, the mathematical model is established at first. The system mainly consists of an inserting tube and a tube tip, which are modeled based on a moving flexible beam and a soft robot, respectively. In order to reduce the harm to the patient during the operation, the robot system should suppress the vibration of the inserting tube during the process of tracking the desired trajectory in the bronchus. Therefore, we use the boundary control algorithm to design a controller capable of suppressing vibration for the inserting tube. Meanwhile, in order for the robot system to accurately select the bronchus corresponding to the branch, we designed a soft robot controller that can bend or deflect the soft robot to a specified posture. Finally, we used theoretical proof and numerical simulation to verify the conclusion.